Influence of k-casein genotype on heat stability and cheese making properties of milk powder - Alexandr Gennadyevich Kruchinin; Elena Evgenyevna Illarionova; Alana Vladislavovna Bigaeva; Svetlana Nikolaevna Turovskaya (Mljekarstvo)
In this study the effect of k-casein gene polymorphism on the technological characteristics of milk powder obtained by spray (AA1:BB1) and freeze drying (AA2:BB2) was investigated. Standardized and generally accepted methods were used in the field of physical and chemical control of dairy products, as well as methods for assessing the heat stability and cheese making properties of milk. The most heat-resistant were the samples with a predominance of milk obtained from cows with the AA CSN3 genotype, in the pH range from 6.4 to 7.0 (36-91 minutes for AA1:BB1 and 37-101 minutes for AA2:BB2). In systems with a fraction of 25% to 100% of milk from cows with the AA CSN3 genotype obtained by freeze drying, higher (by 3-10%) stabilization qualities of protein were revealed when heated in the pH range from 6.4 to 7.0 compared to spray drying. The analysis of the results regarding the cheese making properties showed that with an increase in the proportion of milk from cows with the BB CSN3 genotype from 0% to 100% in model systems, the rennet coagulation time decreases for all samples, regardless of the drying method. It was also found that when using freeze drying, coagulum of all samples were assigned to the highest class of milk quality in terms of cheese making properties, while during spray drying only the samples consisting of min. 75% or completely of milk obtained from cows with genotype BB CSN3 corresponded to this category.